2014
DOI: 10.1007/s00784-014-1321-3
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and late analysis of dental pulp stem cells viability after indirect exposition to alternative in-office bleaching strategies

Abstract: This study presents proposals for in-office dental bleaching to be performed with limited aggressive effect on dental pulp stem cells. Therefore, we are able to offer interesting clinical alternatives for bleaching vital teeth, under professional supervision, maintaining the integrity and reparative capacity of pulp-dentin complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 28 publications
(82 reference statements)
0
43
0
1
Order By: Relevance
“…In future studies, the best application time should be determined, as well as intervals between sessions to achieve better performance of the compound with minor adverse effects. 27,28 Subjective outcomes measured by the variation of SGU units are shown to be inconsistent with the objective results. The subjective determination of tooth colour is challenged by high variability.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In future studies, the best application time should be determined, as well as intervals between sessions to achieve better performance of the compound with minor adverse effects. 27,28 Subjective outcomes measured by the variation of SGU units are shown to be inconsistent with the objective results. The subjective determination of tooth colour is challenged by high variability.…”
Section: Discussionmentioning
confidence: 92%
“…10 Soares et al recently reported on low-concentration (17.5%) and short-duration applications and found significantly reduced cellular damage under in vitro conditions. [12][13][14] There is interest in RCTs to assess compounds with lower concentration that would comply with standards such as those of the European Community. The objective of this work is to show the effectiveness of a bleaching gel (6%) catalyzed by titanium dioxide nanoparticles and activated by hybrid light.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Jun‐D is present in pulp tissue during the repair process involving reactionary dentine formation, but its presence during dentine formation following severe loss of odontoblasts caused by intense H 2 O 2 ‐induced oxidative stress (Soares et al . , , Cintra et al . ) has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
“…As oxygen diffuses through enamel and dentin, it may affect the pulp 11,12,18,21,28 and result in tooth sensibility, an adverse effect of toxic components 2,3,12,15,27 . The low molecular weight of hydrogen peroxide promotes tooth bleaching, but also the release of inflammatory mediators into the pulp, which may damage pulp cells 3,12,26,27 .…”
Section: Introductionmentioning
confidence: 99%
“…The low molecular weight of hydrogen peroxide promotes tooth bleaching, but also the release of inflammatory mediators into the pulp, which may damage pulp cells 3,12,26,27 . The rate of hydrogen peroxide penetration differs between bleaching agents and depends on their concentration and time of application as well as on the presence or absence of restorations 3,17,21 .…”
Section: Introductionmentioning
confidence: 99%